2000
DOI: 10.1121/1.428274
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical correlates of contralateral efferent suppression. I. The role of the medial olivocochlear system in “central masking” in nonhuman primates

Abstract: An extensive physiological literature, including experimental and clinical studies in humans, demonstrates that activation of the medial olivocochlear (MOC) efferent system, by either contralateral sound or electrical stimulation, can produce significant alterations in cochlear function and suggests a role for the MOC system in influencing the auditory behavior of binaural hearing. The present data are from psychophysical studies in nonhuman primates which seek to determine if the noted physiological changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Contralateral tones suppress responses of auditory-nerve fiber stimuli near characteristic frequency, but only if the olivocochler bundle is intact (Fex, 1967;Warren and Liberman, 1989). A psychoacoustic study with macaque monkeys indicated that the suppressive effects of central masking could be reduced or eliminated when the MOC bundle was sectioned at the floor of the IVth ventricle (Smith et al, 2000). On the other hand, the bilateral CI subjects in the present report demonstrated central masking despite lacking efferent outer hair cell modulation in their electrically stimulated inner ears.…”
Section: Discussionmentioning
confidence: 50%
“…Contralateral tones suppress responses of auditory-nerve fiber stimuli near characteristic frequency, but only if the olivocochler bundle is intact (Fex, 1967;Warren and Liberman, 1989). A psychoacoustic study with macaque monkeys indicated that the suppressive effects of central masking could be reduced or eliminated when the MOC bundle was sectioned at the floor of the IVth ventricle (Smith et al, 2000). On the other hand, the bilateral CI subjects in the present report demonstrated central masking despite lacking efferent outer hair cell modulation in their electrically stimulated inner ears.…”
Section: Discussionmentioning
confidence: 50%
“…There is a small amount of behavioral data from animal studies showing efferent-mediated changes in response to sound. Smith et al (2000) found that contralateral noise raised behavioral thresholds for tones in Japanese macaques, and that this effect disappeared with sectioning of the medial olivo-cochlear bundle. May and McQuone (1995) reported that cats showed a decrease in the ability to detect intensity changes in 8-kHz tones presented in ipsilateral noise after sectioning of the medial olivocochlear bundle.…”
Section: Discussionmentioning
confidence: 99%
“…In four guinea pigs, only one of the agents was used at the same dosages. In two awake guinea pigs, gentamicin was administered at 200 mg/kg IM in order to achieve a pharmacological block of the MOC reex (Smith et al 1994;Avan et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Second, gentamicin, a known blocker of the MOC re¯ex (Smith et al 1994;Avan et al 1996) also greatly reduces these adaptations in guinea pig (Fig. 2).…”
Section: Dpoae Adaptation As a Metric For Moc Re¯ex Strengthmentioning
confidence: 96%
See 1 more Smart Citation